Membentuk Karakter Kepemimpinan Bagi Siswa Kelas XII SMK Marsudirini ST Fransiskus Semarang - Puspita Puji Rahayu (Jurnal Kabar Masyarakat, 2023)
This activity is in the form of dissemination of leadership character for students of Franciscan Semarang Vocational School, in order to provide opportunities for individuals who wish to deepen their understanding of leadership and improve leadership skills. The goal in this community service is that participants are expected to be able to grow individual characters with leadership and high integrity, especially in organizational management. The method used in this training is in the form of lecture activities, question and answer sessions, case study discussions, by explaining the basic concepts of leadership, leadership styles, differences between leaders and bosses and how to make the right decisions. The results of the community service show the smooth running of the activities and the enthusiasm of the participants in participating in a series of activities and showing activeness by asking a number of questions during the discussion and question and answer sessions.